Alternating poly(lactic acid)/poly(ethylene-co-butylene) supramolecular multiblock copolymers with tunable shape memory and self-healing properties1. Issue 32 (28th August 2015) - Chang, Ruoxing; Huang, Yongfeng; Shan, Guorong; Bao, Yongzhong; Yun, Xueyan; Dong, Tungalag; Pan, Pengju
<x xml:space="preserve">Abstract</x> PLA/PEB SMPs with tunable shape memory and self-healing properties were prepared by end functionalization of PLA–PEB–PLA with UPy units.